Nucleic Acid Synthesis in Cytoplasm of Yaba Monkey Tumor Virus-Infected Cells - Rouhandeh, H. (1973)
Yaba tumor virus progeny appeared in cynomolgus monkey kidney cells at 24 h postinfection and reached a plateau at 72 h in the first cycle of replication. Viral DNA synthesis was first detected at about 3 h and reached a peak in 18 h. Maximum coating of viral DNA in infected cells occurred at 4 days postinfection. Rapidly labeled RNA was synthesized in the cytoplasm of virus-infected cells. At 6 h postinfection 7 to 10S RNA was present; this species was present in greater amount at 12 h; at 24 h a truncated peak indicated the presence of 14 to 15S as well as 7 to 10S RNA. Hybridization data indicated that the largest peak of messenger RNA synthesis occurred at 11 to 13 h postinfection and a second, slightly smaller, peak occurred at 21 to 23 h.